Drug-induced orthostatic hypotension: A systematic review and meta-analysis of randomised controlled trials. - Cini Bhanu (Public Library of Science (PLoS), 2021)
Background Drug-induced orthostatic hypotension (OH) is common, and its resulting cerebral hypoperfusion is linked to adverse outcomes including falls, strokes, cognitive impairment, and increased mortality. The extent to which specific medications are associated with OH remains unclear. Methods and findings We conducted a systematic review and meta-analysis to evaluate the extent to which specific drug groups are associated with OH. EMBASE, MEDLINE, and Web of Science databases were searched from inception through 23 November 2020. Placebo-controlled randomised controlled trials (RCTs) on any drug reporting on OH as an adverse effect in adults (≥18 years) were eligible. Three authors extracted data on the drug, OH, dose, participant characteristics, and study setting. The revised Cochrane risk-of-bias tool for randomised trials (RoB 2) was used to appraise evidence. Summary odds ratios (ORs) were estimated for OH using fixed effects Mantel-Haenszel statistics. We conducted subgroup analysis on validity of OH measurement, drug dose, risk of bias, age, and comorbidity. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) tool was used to summarise the certainty of evidence. Of 36,940 citations, 69 eligible RCTs were included in the meta-analysis comprising 27,079 participants. Compared with placebo, beta-blockers and tricyclic antidepressants were associated with increased odds of OH (OR 7.76 [95% CI 2.51, 24.03]; OR 6.30 [95% CI 2.86, 13.91]). Alpha-blockers, antipsychotics, and SGLT-2 inhibitors were associated with up to 2-fold increased odds of OH, compared to placebo. There was no statistically significant difference in odds of OH with vasodilators (CCBs, ACE inhibitors/ARBs, SSRIs), compared to placebo. Limitations of this study are as follows: data limited to placebo-controlled studies, (excluding head-to-head trials), many RCTs excluded older participants; therefore results may be amplified in older patients in the clinical setting. The study protocol is publicly available on PROSPERO (CRD42020168697). Conclusions Medications prescribed for common conditions (including depression, diabetes, and lower urinary tract symptoms) were associated with significantly increased odds of OH. Drugs causing sympathetic inhibition were associated with significantly increased odds of OH, while most vasodilators were associated with small nonsignificant differences in odds of OH, compared to placebo. Drugs targeting multiple parts of the orthostatic blood pressure (BP) reflex pathway (e.g. sympathetic inhibition, vasodilation, cardio-inhibitory effects) may carry cumulative risk, suggesting that individuals with polypharmacy could benefit from postural BP monitoring.